(untitled) (The Research of Medical Science Review, 2024)
Background: Minimally invasive techniques (MITs) have revolutionized maxillofacial surgery, offering enhanced precision, reduced recovery times, and improved outcomes in both trauma reconstruction and cosmetic procedures. Advanced surgical methods, including endoscopic-assisted procedures, robotic surgery, 3D imaging, and laser-based technologies, have been pivotal in these advancements.Objective: This study aims to assess the efficacy of MITs in maxillofacial trauma and cosmetic surgery by evaluating surgical precision, healing times, aesthetic results, and postoperative complications.Methods: A retrospective and prospective observational study was conducted, involving patients undergoing minimally invasive procedures for trauma reconstruction (e.g., orbital fractures) and cosmetic surgeries (e.g., rhinoplasty). Data was collected on primary outcomes (surgical precision, healing times, aesthetics, functional recovery) and secondary outcomes (postoperative complications). Statistical analyses, including paired t-tests and ANOVA, were performed to compare MITs with traditional methods. Results: Results demonstrated significantly improved surgical precision, faster healing times, enhanced facial symmetry, and reduced scarring in the MIT group compared to traditional techniques. Postoperative pain and complication rates were lower for MIT patients. These outcomes were validated using clinical evaluations, imaging studies, and patient surveys.Conclusion: Minimally invasive techniques significantly improve both functional and aesthetic outcomes in maxillofacial surgery. Their application leads to quicker recovery, reduced complications, and greater patient satisfaction, establishing them as the preferred approach in many clinical settings.